A high-saturated, long-chain fatty acid ketogenic diet negatively impacts visual and motor-sensory function in a pre-clinical model of multiple sclerosis - Capper, Erin N.; Anders, Jeffrey J.; Elwood, Benjamin W.; Kardon, Randy H.; Gramlich, Oliver W. (Frontiers in Immunology, 2025)
IntroductionMultiple sclerosis (MS) is a neurodegenerative condition that results in demyelination of the central nervous system. Visual impairment, retinal nerve fiber layer thinning, and impaired electrical function in retinal ganglion cells are seen throughout disease progression and serve as useful markers for treatment success. Current research examining the effects of ketogenic diet (KD) as cotherapy show promising anti-inflammatory properties, but research remains limited by differences in experimental set-up and KD composition. The purpose of our study was to use functional and structural biomarkers to determine the neuroprotective effects of a KD composed of long-chain, saturated fatty acids and how the timing of its implementation impacts these biomarkers in an experimental autoimmune encephalomyelitis (EAE) model.MethodsEAE was induced in 80 female C57BL/6J mice by immunization with MOG35-55 and randomly assigned to stay on the standard diet or to start the KD at one of three time points (preconditioned, prophylactic, or late). Motor-sensory scores, visual acuity, OCT, electrophysiology, and histopathology were performed.ResultsIn general, our results show that a KD with long-chain, saturated fatty acids did not significantly improve visual outcomes, and that early implementation of the diet modestly exacerbated motor-sensory and visual acuity deficits despite not impacting optic nerve axonal damage, retinal ganglion cell loss, or psychomotor measurements of visual system function.DiscussionWe propose that the anti-inflammatory neuroprotective benefits of a KD are limited when saturated, long-chain fatty acids are used, and that chain length and fat saturation should be taken into account when utilizing KD as a treatment.